MUATAN TRADISI DALAM IKLAN TV INDONESIA - Murtono, Taufik (Seni Media Rekam ISI Surakarta, 2009)
In the advertising industry, the workers have to birth the interesting and fresh ideas in order to communicate the products. The interesting and fresh ideas need the highly creativity. The need to be a high creative creator causes the idea that is differently anyway and irrelevant with the characteristic of the products. The course of traditional content Indonesian advertising have been arouse several years ago nevertheless there is still very limit advertising in which uses the content of the tradition.Â Keyword : traditional content, commercial